The Effect of Digital Flashcard on Students’ Vocabulary Mastery - Triwahyu, Triwahyu; Manurung, Konder; Patmasari, Andi; Thamrin, Nur Sehang (Journal of English Language and Education, 2025)
This research aims to enhance the vocabulary mastery of seventh-grade students by applying digital flashcards in English learning at SMP Negeri 20 Palu. A quasi-experimental research design with a non-equivalent control group was employed. The population comprised 106 seventh-grade students, and the samples were selected using cluster random sampling, with class VII A assigned as the experimental group and class VII B as the control group. Data collection was carried out through pre-tests and post-tests to examine students’ improvement in vocabulary mastery. The findings revealed that students in the experimental group obtained a higher average post-test score (72.00) compared to those in the control group (56.13). Statistical analysis conducted using SPSS version 25 showed a significance value of p = 0.000, which is lower than 0.05, indicating that the alternative hypothesis was accepted. These results confirm that digital flashcards are effective in improving students’ vocabulary mastery. Furthermore, the pedagogical implications of this research indicate that integrating digital media into vocabulary instruction can foster students’ motivation, active participation, and independent learning, while also supporting the adoption of technology-based teaching practices in the classroom.